2011
DOI: 10.1111/j.1365-246x.2011.05134.x
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake precursors: activation or quiescence?

Abstract: S U M M A R YWe discuss the long-standing question of whether the probability for large earthquake occurrence (magnitudes m > 6.0) is highest during time periods of smaller event activation, or highest during time periods of smaller event quiescence. The physics of the activation model are based on an idea from the theory of nucleation, that a small magnitude earthquake has a finite probability of growing into a large earthquake. The physics of the quiescence model is based on the idea that the occurrence of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

6
3

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 52 publications
4
8
0
Order By: Relevance
“…Following the results in Ref. [34], we concluded that a new model for earthquake probabilities was needed, leading to the model described in this paper.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Following the results in Ref. [34], we concluded that a new model for earthquake probabilities was needed, leading to the model described in this paper.…”
Section: Discussionsupporting
confidence: 58%
“…Are large earthquakes more probable during times of increased seismic activity (activation) or during times of decreased seismic activity (quiescence)? We have considered this question at length [34] and find no compelling evidence for either assumption. We concluded that earthquake probabilities computed from rates of activity are not statistically significant as compared to Poisson probabilities.…”
Section: Discussionmentioning
confidence: 88%
“…This problem of false-positive indications, very common to hazards forecasting, is typically addressed by raising or lowering a detection threshold to optimize a probability gain metric (JOLLIFFE and STEPHENSON, 2003;RUNDLE et al, 2011;USGS-CSEP, 2013). As we will discuss, in addressing item 3, this ''threshold'' approach probably does not apply directly to the RBTS method, as there does not seem to be an obvious pattern to the amplitude or duration of periods in which r\1, from Eq.…”
Section: Noise and False Indicationsmentioning
confidence: 99%
“…As mentioned above, besides b-value measurements, the seismicity-rate changes, which may be associated with the physical properties of the seismogenic zone, could be useful precursors for the main future shocks. Rundle et al [28] have discussed the longstanding question on the highest occurrence probability of large earthquake (M > 6:0) during the time periods of smaller event activation or smaller event quiescence. Their results led to the conclusion that California seismicity was more likely characterized by quiescence than activation.…”
Section: Introductionmentioning
confidence: 99%